A field efficacy trial of a trivalent vaccine containing porcine circovirus type 2a and 2b, and Mycoplasma hyopneumoniae in three herds. Issue 2 (22nd October 2021) - Um, Hyungmin; Yang, Siyeon; Oh, Taehwan; Cho, Hyejean; Park, Kee Hwan; Suh, Jeongmin; Chae, Chanhee
Abstract: Background: This field trial was designed to evaluate the efficacy of a new trivalent vaccine containing porcine circovirus type 2a and 2b (PCV2a/b), and Mycoplasma hyopneumoniae at three independent locations. Methods: Three farms were selected based on their history of PCV2 and M. hyopneumoniae co‐infection. Each farm housed a total of 60, 3‐day‐old pigs that were randomly allocated to one of three treatment groups. Pigs were administered the trivalent vaccine intramuscularly with either a 1.0 ml dose at 3 and 24 days of age or a 2.0 ml dose at 21 days of age in accordance with the manufacturer's recommendations. Results: Clinically, the average daily weight gain of the one‐dose and two‐dose vaccinated groups within all three farms was significantly higher ( p  < 0.05) than those of unvaccinated animals during the growing (70–112 days of age), finishing (112–175 days of age) and overall (3–175 days of age) stages of production. One‐dose and two‐dose vaccinated animals elicited neutralizing antibodies and interferon‐γ‐secreting cells (IFN‐γ‐SC), which reduced the amount of PCV2 in terms of blood load and reduced the severity of lymphoid lesions when compared with unvaccinated animals. Similarly, one‐dose and two‐dose vaccinated animals elicited IFN‐γ‐SC, which reduced the amount of M. hyopneumoniae in terms of laryngeal load and reduced the severity of lung lesions. Conclusions: The intramuscular administration of either one or two doses of trivalent vaccine was not significantly different in any of the evaluated parameters. The results of field trial demonstrated that the trivalent vaccine was efficacious in the protection of swine herds where PCV2d and M. hyopneumoniae were in active circulation. Abstract : This field trial was designed to evaluate the efficacy of a new trivalent vaccine containing porcine circovirus type 2a and 2b (PCV2a/b), and Mycoplasma hyopneumoniae at three independent locations.